A comprehensive reasearch of the impact of growth stimulators and microbiofertilizer on the productivity of winter wheat - N. I. Mamsirov; A. A. Mnatsakanyan; A. V. Zagorulko; A. A. Makarov (Новые технологии)
In agrotechnologies for the cultivation of field crops, plant growth regulators, as well as microbiofertilizers can have a beneficial effect on soil microflora, without leading to environmentally unfavorable consequences for the biosphere. The economic efficiency of the production of grain crops, in particular, winter wheat, is also significantly increasing. The article presents the results of many years of research on a comprehensive study of adaptation parameters, innovative elements that exist today in relation to the technology of growing winter wheat in the foothills of the Republic of Adygea. Namely, preparations intended for the fullest possible disclosure of the yield potential of the cultivated crop, Alfastim, Agrostimulus growth stimulants and Ecobacter- Terra microbiofertilizers. The objectives of the research are to study the directions and extent of the impact of micro-, bio-fertilizers and plant growth regulators on the sowing qualities of winter wheat; establishment of characteristic changes in the subsequent processes of growth and development of culture due to the use of the studied drugs; identification and analysis of data on the yield of winter wheat treated with the studied preparations; comprehensive assessment of the effectiveness of the use of Ecobacter-Terra microbiofertilizer and Alfastim, Agrostimul growth regulators in the process of growing winter wheat. As a result of the research, it has been proved that in the conditions of the foothills of Adygea, when growing winter wheat, it is considered profitable and economically justified to apply nitrogen fertilizer at a dose of N70 in the early spring, along with the use of Alfastim growth regulator in the form of seed treatment 25 g/t + crops in the phase tillering 25 g/ha + crops in the heading phase 25 g/ha). These elements of cultivation technology make it possible to increase the yield up to 7.35 t/ha (+0.83 t/ha to the control) and receive an additional net income of 7732.2 rubles/ha.The studies were carried out on the equipment of the «Expert» Common Use Center of FSBEI HE «MSTU».